The Interactive Role of Physical Activity and Personality Traits in Psychosocial Status of Elders - Behrouz Abdoli; Parvaneh Shamsipour Dehkordi; Amir Shams (University of Social Welfare & Rehabilitation Sciences, 2009)
Objectives: The main purpose of this study was to determine the interactive role of physical activity and personality traits inpsychosocial development of elders. Methods & Materials: This research was a casual comparative with 300 elders (150 active and 150 non-actives) with 60-85 years old from Tehran selected as statistical sample on available bases. All subjects completed psychosocial development questionnaire (MPD) and Eysenk personality traits questionnaire (EPI). Data were analyzed with using descriptive statistic (mean and standard deviation) and inferential statistic (t-test and Factorial ANOVA) with SPSS soft ware Vr.11.5 on P<0.05 . Results: Data showed that 70% of active and 68% of non-active elders were in range of 60-70 years old, 55% of active and %53.3 of non active elders had completed high school and 46.7% of active and 56.7% of non-active elders were moderate level, considering economicalcondition. The level of personality traits (extroversion-introversion and stable-unstable personality traits) and psychosocial development in active elders were higher than non-active elders and active elderswith extroversion and stable traits were in higher psychosocial status. Conclusion: The finding of this research showed that physical activity modifies the interaction between personality traits and psychosocial development. Therefore, active living style in life span, probably with the effect of positive personality traits, could postponephysical and psychosocial regression during aging.